Effects of loop type and target direction variation on kinematics and kinetics of table tennis backhand loop: a statistical parametric mapping approach - Li, Zheng’ao; Wang, Liangsen; Zhang, Ling; Hou, Ying; Sun, Yuliang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundModern table tennis increasingly relies on the backhand loop as a primary scoring stroke, but it remains unclear whether commonly used tactical variants—Fast-Loop versus Slow-Loop and Long-Line versus Cross-Court—place different demands on lower-limb kinetics and performance-related kinematics. This study aimed to analyse differences in backhand loop against backspin techniques among elite male table tennis players, focusing on various loop types and variations in target direction.MethodsFifteen elite table tennis athletes performed the backhand loop. Kinematics and kinetics variables were collected synchronously. The racket velocity, joint angles of the upper and lower limbs, and torques at the lower limb were calculated and analysed using SPM1d two-way repeated measures ANOVA among the stroke phases.ResultsThe hip extension torque of fast-loop was significantly higher than that of slow-loop during the early phase of the stroke (p < 0.001). Target direction changes of the loop were dependent on early elbow flexion (p = 0.015) and middle trunk rotation (p < 0.001) during the stroke phase. The fast-loop and cross-court of loops imposed a greater holding-side lower-limb load during the follow-through phase (p < 0.001, p = 0.032).ConclusionLower-limb drive strategies differed between Fast-Loop (FL) and Slow-Loop (SL) in the non-holding limb. FL emphasized hip-extension torque, whereas SL emphasized knee-extension torque. Compared with Long-Line, Cross-court relied on more trunk rotation, with no additional lower limb contribution. However, FL and CC imposed higher loads on the holding lower limb during the follow-through. Practitioners should emphasize lower-limb strength and neuromuscular control to ensure loop quality and monitor follow-through braking loads, which can increase lower-limb injury risk when excessive.